Peningkatan Aktifitas dan Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti Pada Siswa Kelas IV SD Negeri 16 Kampung Nan VI - Rahmadani Fitri, Yunita (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to improve student activity in Islamic Religious Education (PAI) and Character Education (BP) through the implementation of the Team Games Tournament (TGT) learning model. The research was conducted in two cycles, with each cycle consisting of planning, implementation, and reflection stages. The results of the study show that the first cycle faced some challenges, particularly in increasing students’ courage to ask questions and express ideas. Therefore, improvements were made in the second cycle, such as providing rewards and changing groups to enhance student interaction. The results of the second cycle showed significant improvements in students’ positive activities, such as paying attention to the lesson, taking notes, asking questions, and answering questions. Although there were some negative activities, such as joking, overall, the TGT model successfully improved the quality of learning and student engagement.